Kesesuaian Laboratorium Biologi sebagai Penunjang Pembelajaran Biologi di SMA Muhammadiyah se-Surakarta dengan Standar Laboratorium Biologi - Putri Agustina1; Alanindra Saputra2; Lina Mufidatun Qonitat1; Runing Dwi Utami1; Yohana Yohana1 (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Biology Learning can not be separated from the lab. Practicum is one of the method of Biology learning which gives opportunity for students to experience themselves, follow a process, observe an object, analyze, prove, and draw their own conclusions about a certain object, situation, or process. This study aims to analyze the suitability of Biology laboratory in SMA Muhammadiyah in Surakarta with Permendiknas Nomor 24 Tahun 2007 about Education Facilities and Infrastructure Standards. The laboratory observed was the Biology laboratory at SMA Muhammadiyah 1, 2, and 3 Surakarta. The research was conducted in September 2017 until January 2018. Data in the form of laboratory observation result obtained by observation, documentation, and interview. The results showed that in general, the quality of Biology laboratory in SMA Muhammadiyah in Surakarta was in good category with average percentage of 78.17%. Aspects observed include laboratory space, laboratory furniture, educational equipment, experimental tools and materials, educational media, consumables, other equipment, and laboratory managers.